Implementation of control valves system on microturbine drone’s rotational motion - Muhamad Nazri, Muhammad Nor Ikmal; Basri, Adi Azriff; Basri, Ernnie Illyani; Singh, Spoorthi (Penerbit Akademia Baru, 2024)
The drone technology has received a wide range of research focusing on improving flight dynamics, battery life, payload capacity and sensor technology. However, for the applications of using drone for high rise buildings are limited by battery life for longer flight with longer duration tasks. This work presents the implementation of a control valve systems for the rotational motion of a microturbine drone. The first objective of this project was to design and develop a control valve system for a microturbine with propeller. The second objective was to measure micro turbine’s performance output which consisted of revolution per minute (rpm) and voltage (V) produced with the control valves system. The final objective was to verify the effectiveness of the control valve system by measuring the differences of the turbine speed of each turbine on the quadcopter to conceptually control the rotational motion of the drones. In conclusion, this work demonstrated the concept of the developed control valve system that can control the rotational motion of the drone.